Pengaruh Trade Creation dan Trade Diversion pada ACFTA terhadap Ekspor Karet (HS 40) Indonesia - Qur'ani, Nissa Shahadah; Utami, Efri Diah (Politeknik Statistika STIS, 2023)
Indonesia is one of the highest exporters of rubber and articles thereof. In utilizing natural resources, Indonesia joined ASEAN China Free Trade Area (ACFTA), the agreement ASEAN and China to create a free trade area. There are effects of trade union, trade creation and diversion. This study aims to find out the general description of rubber and articles thereof exports, trade patterns before and after implementation of ACFTA, and variables that can affect Indonesia's exports of rubber and articles thereof. This study uses the SUR model gravity fixed effects panel with data 2000-2021. The trading pattern showed indications of changes before and after ACFTA; variables of real GDP per capita, economic distance, population, REER, measures of economic similarity, trade creation and diversion affect Indonesia's exports rubber and articles thereof; and no trade creation or diversion effects were found. So, it is better for Indonesia expand exports to non-ACFTA members countries.